1993
DOI: 10.1002/etep.4450030110
|View full text |Cite
|
Sign up to set email alerts
|

Current compensation in three‐phase power systems

Abstract: In this paper the compensation of reactive and unbalanced currents in three‐phase power systems is discussed. The main result proved is that in sinusoidal steady state any current which corresponds to zero total active power can be compensated by means of a reactive element; the compensation of the reactive currents and the compensation of the unbalanced currents in three‐phase power systems are special cases of this result. The explicit expression of the compensating reactances is derived and the multiplicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 4 publications
1
12
0
3
Order By: Relevance
“…The present paper generalizes a result of [1] for three-phase systems to an arbitrary number of phases. It is shown that the reactive compensation element does not require elements between any pair of phases, which would be the straightforward generalization of the results of [1]; it is sufficient to have a star-connected and a circular-connected part.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The present paper generalizes a result of [1] for three-phase systems to an arbitrary number of phases. It is shown that the reactive compensation element does not require elements between any pair of phases, which would be the straightforward generalization of the results of [1]; it is sufficient to have a star-connected and a circular-connected part.…”
Section: Resultsmentioning
confidence: 69%
“…It does not require elements between all pairs of phases (which would be the straightforward generalization of the results of [1]); it is sufficient to have a star connected and a circular connected part (that is a scheme with connections only between adjacent phases).…”
Section: Introductionmentioning
confidence: 99%
“…Explicitly: "Find the compensator current which corresponds to zero instantaneous power and which is as small as possible, considering this constraint." The solution can be found in the literature [11], [15], [17], [18], [21]. The second question is dealt with in the next section.…”
Section: Instantaneous Power Analysismentioning
confidence: 99%
“…It is rather obvious that the reactive current component can be generated by means of a set of inductors and capacitors. It has been shown that also the unbalanced current can be generated by inductors and capacitors [6], [18]. The Steinmetz compensation of a single-phase resistive load is a classical example of such compensator.…”
Section: Sinusoidal Voltagesmentioning
confidence: 99%
See 1 more Smart Citation